Fruit characteristics and phenology Tahiti lime in two Colombian environments - Arias-García, Juan Sebastián; Hurtado-Salazar, Alejandro; Ceballos-Aguirre, Nelson; Ramirez-Castillo, Mariana; Villegas-Noreña, Laura Elisa (Revista de Ciencias Agrícolas, 2023)
The surge in Tahiti lime exports over the past year, combined with heightened quality standards of the international market, have made it necessary to improve production processes to obtain fruit with increasingly better organoleptic characteristics. Thus, the foundation lies in selecting a property with suitable edaphoclimatic conditions and possessing precise knowledge of the ecophysiological behavior of the tree in these specific conditions. This study aimed to document the flowering phenology and study the physicochemical characteristics of Tahiti lime fruits in two environments in the Andean region of Colombia. Evaluations were conducted on eight Tahiti lime trees (ten-year-old) per orchard grafted on Sunki x English. Observations were made for 12 months of the buds, flowers and fruits of the marked trees in each evaluated area (Manizales – 2280 m asl and Santagueda 1010 m asl). The flowering phenology according to the stages of the BBCH phenological scale, the physical-chemical characteristics of the fruit, and the climatic conditions of the two areas were evaluated. A completely randomized experimental design and Duncan’s comparison of means were used. Significant differences were found in polar diameter, ascorbic acid, soluble solids, juice yield, shell mass, and titratable acidity according to locality. The Phenology of flowering took less time, and the accumulation of heat units was higher in the lower altitude zone. The physical and chemical characteristics of Tahiti lime fruits are influenced by the environment in which the trees develop.